Preparation method and application of Prussian blue material

The surface modification of Prussian blue materials is achieved through the gradient precipitation method, which solves the problems of high moisture content and poor interface stability of the material, improves the material's capacity, moisture resistance and cycle stability, and achieves a more uniform modification effect.

CN119320151APending Publication Date: 2025-01-17XIAMEN THREE CIRCLES BATTERY CO LTD

Patent Information

Application Number
CN202411221356.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Prussian blue cathode materials are synthesized in the aqueous phase and have high moisture content, which affects the specific capacity and safety performance of the battery, and have poor interface stability with the electrolyte, resulting in the dissolution of active metal ions and the growth of sodium dendrites, affecting the performance of the battery.

Method used

The gradient precipitation method is used to mix ferrocyanide and transition metal salt solution in the base liquid by dripping addition, and the solution to be doped with alkali metal and transition metal ions is added to achieve the concentration of alkali metal ions and transition metal ions. The gradient changes directly to complete the surface modification during the precipitation process to avoid subsequent wet coating processes.

Benefits of technology

The material's gram capacity, voltage platform, moisture-proof performance and cycle stability are improved, and the uniform modification effect is better than traditional methods, enhancing the moisture-proof performance and rate-proof performance of Prussian blue materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320151A_ABST
    Figure CN119320151A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a prussian blue material, and belongs to the field of battery materials.The preparation method of the prussian blue material comprises the following steps that S1, a solution containing ferrocyanide is prepared to serve as a raw material A, a solution containing transition metal salt is prepared to serve as a raw material B, a to-be-doped solution C containing alkali metal ions is prepared, the method comprises the following steps: S1, preparing a to-be-doped solution C containing transition metal ions, S2, adding a base solution into a container, continuously adding the raw material A and the raw material B into the base solution, and stirring and mixing to form a precipitate, and S3, in the precipitation process, continuously adding the to-be-doped solution C into the raw material A and continuously adding the to-be-doped solution D into the raw material B until the precipitation is finished to obtain the Prussian blue material. According to the invention, the moisture resistance, the rate capability and the cycle stability of the Prussian blue material are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of battery materials, and in particular relates to a preparation method and application of a Prussian blue material. Background Art

[0002] Prussian blue-based cathode materials have attracted widespread attention due to their unique framework structure and low cost. They have the following advantages when used as cathode materials for sodium-ion batteries or potassium-ion batteries: (1) High specific capacity, capable of reversible extraction / embedding of two sodium or potassium ions, with a theoretical specific capacity of 170 mAh / g. (2) Structural stability: Due to the high coordination stability constant of Fe-CN, Prussian blue-based compounds have three-dimensional structural stability, which helps maintain the structural integrity of the battery during charging and discharging. (3) Prussian blue-based compounds are easy to prepare, and the transition ions in the framework are environmentally friendly and low in cost. (4) Excellent rate performance: Prussian blue-based compounds exhibit good rate performance, which enables the battery to withstand rapid charging and discharging. On the other hand, some shortcomings have been exposed in its actual application process. The first one is the crystal water problem. Since Prussian blue compounds are synthesized in the water phase and have not been sintered at a high temperature of more than 300°C, these crystal waters may occupy the sodium and potassium storage sites and the sodium and potassium ion deintercalation channels, affecting the specific capacity and coulomb efficiency of the material; more seriously, a water content greater than 1000ppm will cause continuous gas production during the formation and circulation of the battery cell and even during static conditions, which seriously affects the safety performance of the battery. In addition, the poor interface stability between the Prussian blue material and the electrolyte and related side reactions cause the active metal ions to dissolve in the electrolyte, which deteriorates the battery cycle performance, and the growth of sodium dendrites will also affect the battery performance.

[0003] In order to overcome these shortcomings, researchers are exploring different modification strategies, such as improving the electrochemical performance by adjusting the preparation method, metal ion doping and surface coating, etc. All of the above processes are usually cumbersome and will increase the production process and cost. Therefore, it is very important to find a simple and efficient synthesis modification process to improve the shortcomings of Prussian blue cathode materials.

[0004] Conventional gradient positive electrode materials only have gradient changes for transition metal ions such as cobalt, nickel, manganese, iron, etc., such as a lithium-ion battery positive electrode material preparation method and its application with application number CN201610835895.X, and a lithium-ion battery positive electrode material with full gradient concentration distribution and its preparation method with application number CN202010392804.6. And the gradient change trend is relatively single, while the concentration of alkali metal ions such as lithium, sodium, potassium, etc. in the material remains fixed.

[0005] Conventional Prussian blue materials, taking the sodium positive electrode Na2Mn(CN)6 as an example, during the charge and discharge process, sodium ions are inserted and removed, manganese ions gain and lose electrons, the valence state changes between divalent and trivalent, and provides a charge and discharge platform of about 3.4V. However, the disadvantage of this material is that the water content is greater than 10wt%. Even if it is vacuum dried at 180-200℃ for more than 48h and placed in the air (humidity greater than 60%), it will still re-absorb moisture to more than 90% of the original water content within 4 hours, which brings more inconvenience to the storage and application of Prussian blue materials. If potassium ions with larger ionic radius are used to fill the gaps in the framework, it will make it difficult for external water molecules to enter, but too many potassium ions will cause the framework structure to become more distorted and deteriorate the cycle performance of the material, so the control of potassium doping is crucial. On the other hand, the voltage platform (3.4V) of manganese-based materials is better than that of iron-based materials (2.7V) with better cycle, which can greatly improve the energy density of the battery cell. However, the universal existence of manganese ions in electrochemical systems causes them to dissolve and be lost in the electrolyte during the cycle, resulting in the deterioration of the battery's gram capacity, cycle performance, internal resistance, etc. Conventional doping or coating is not only cumbersome, but also reduces the battery platform or the material's gram capacity. Summary of the invention

[0006] The purpose of the present invention is to provide a preparation method and application of a Prussian blue material to overcome at least one of the above-mentioned defects in the prior art.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] The invention provides a method for preparing a Prussian blue material, comprising the following steps: S1: preparing a solution including ferrocyanide as a raw material A, preparing a solution including a transition metal salt as a raw material B, preparing a to-be-doped solution C including alkali metal ions, and preparing a to-be-doped solution D including transition metal ions; S2: adding a base liquid into a container, continuously adding the raw materials A and B into the base liquid, and stirring and mixing to form a precipitate; S3: during the precipitation process, continuously adding the to-be-doped solution C into the raw material A so that the concentration of the alkali metal ions in the raw material A presents a gradient change, continuously adding the to-be-doped solution D into the raw material B so that the concentration of the transition metal ions in the raw material B presents a gradient change, until the precipitation is completed, thereby obtaining the Prussian blue material.

[0009] Preferably, raw material A includes at least one of sodium ferrocyanide solution, potassium ferrocyanide solution, and lithium ferrocyanide solution, with a molar concentration of 0.1-1 mol / L, the temperature of raw material A is 20-80°C, raw material B includes one or more mixed solutions of sulfates of manganese, iron, cobalt, nickel, zinc, and copper, with a molar concentration of 0.1-3 mol / L, the total molar concentration of alkali metal ions in the doped solution C is 0.1-1 mol / L, and the total molar concentration of transition metal ions in the doped solution D is 0.1-3 mol / L.

[0010] Preferably, the doping ions in the doped solution C include at least one of potassium ions, sodium ions, and lithium ions, and the doping ions in the doped solution D include at least one of manganese ions, iron ions, ferrous ions, cobalt ions, zinc ions, and copper ions.

[0011] Preferably, in step S2, a quantitative amount of raw material A and a quantitative amount of raw material B are continuously added to the bottom liquid by a parallel flow dropwise method, and the precipitation method is intermittent, continuous or semi-continuous, the precipitation period is 1-40h, the precipitation temperature is from room temperature to 80°C, and the stirring speed is 10-1000rpm. A single-layer or double-layer stirring paddle is used for stirring, and the blade forms include paddle stirring, anchor stirring, propulsion, open turbine, disc turbine, or magnetic rotor stirring. A peristaltic pump, a metering pump, a screw pump or a gravity inflow form through a high-level tank is used for dropwise addition, and the flow control device is an electromagnetic flowmeter, a rotor flowmeter or a valve. The concentration equipment used in the discontinuous process is a microporous tube or a suction filtration bottle and a vacuum pump of corresponding size.

[0012] Preferably, the precipitation period is 3-10 hours, and the precipitation temperature is room temperature to 60°C.

[0013] Preferably, the dropping speed of raw material A and raw material B is 30-45 mL / h, the dropping speed of solution C to be doped is 5-110 mL / h, and the dropping speed of solution D to be doped is 10-45 mL / h.

[0014] Preferably, in step S2, after adding the base liquid, a reducing agent, an inert gas, one of a reducing gas, or a mixture of an inert gas and a reducing gas is added to the container, and raw material A and raw material B are added after 2-6 hours, the inert gas is nitrogen or argon, the reducing gas is hydrogen or carbon monoxide, and the reducing agent is ascorbic acid, hydrazine hydrate, sodium sulfite or sodium borohydride.

[0015] Preferably, the base liquid is an aqueous solution, a sodium sulfate solution, a sodium chloride solution or a potassium sulfate solution, the base liquid temperature is from room temperature to 100° C., and the mass concentration of the sodium sulfate solution, the sodium chloride solution or the potassium sulfate solution is 200-450 g / L.

[0016] Preferably, the base liquid also includes a complexing agent with a mass concentration of 0.1-10g / L, and the complexing agent is at least one of trisodium citrate, ammonia water, sodium oxalate, sodium phosphate, sodium pyrophosphate, sodium acetate, ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, sodium manganese ethylenediaminetetraacetate, triethanolethylenediamine, urea, sodium succinate, sodium tartrate, polyvinylpyrrolidone, and polyacrylamine.

[0017] The present invention also provides an application of the Prussian blue material prepared by the above-mentioned Prussian blue material preparation method in preparing a positive electrode material for a battery.

[0018] The beneficial effects of the present invention are:

[0019] The gradient-type Prussian blue derivative positive electrode material synthesized by the method of the present invention is compared with conventional non-gradient materials under the same proportion and composition. The sodium and manganese elements in the core improve the material's gram capacity and voltage platform, the potassium element on the surface improves the material's moisture resistance, and the nickel, cobalt, zinc, copper, iron and other elements on the surface improve the material surface stability and battery cycle performance. The precipitation process is adopted, and the surface modification is completed directly in the precipitation process through the gradient change of alkali metal ions and variable valence transition metal ions from the bulk phase to the surface during the precipitation process, without the need for a subsequent wet coating process, and the surface modification effect is more uniform. The gradient change speed of various metal ions can be adjusted in real time to obtain a product with multiple elements and multiple concentration gradient changes, thereby obtaining a modification effect that is superior to the direct doping of traditional battery materials in raw materials and the coating of finished products, greatly improving the moisture resistance, rate performance, and cycle stability of Prussian blue materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the structure of the synthesis device used in Example 1 of the present invention.

[0021] Figure 2 This is a graph showing the color and moisture changes of the Prussian blue gradient material and the non-gradient material with the same components prepared in Example 1 of the present invention during standing in a 60% humidity environment.

[0022] Figure 3 It is a schematic structural diagram of the Prussian blue material prepared in Example 1 of the present invention.

[0023] Figure 4 This is an electron microscope image of the Prussian blue material prepared in Example 1 of the present invention.

[0024] Figure 5 It is a schematic diagram of the concentration gradient change of the Prussian blue material prepared in Example 1 of the present invention.

[0025] Figure 6It is a comparison chart of the IC cycle performance of sodium ion batteries assembled with the Prussian blue gradient positive electrode material prepared in Example 1 of the present invention and the non-gradient positive electrode material of the same component.

[0026] Figure 7 It is a schematic diagram of the structure of the Prussian blue material prepared in Example 2 of the present invention.

[0027] Figure 8 Schematic diagram of the concentration gradient change of the Prussian blue material prepared in Example 2 of the present invention.

[0028] Fig. 9 This is a comparison chart of the IC cycle performance of sodium ion batteries assembled with the Prussian blue gradient positive electrode material prepared in Example 2 of the present invention and the non-gradient positive electrode material of the same component.

[0029] Fig.10 Schematic diagram of the concentration gradient change of the Prussian blue material prepared in Example 3 of the present invention.

[0030] Fig.11 Schematic diagram of the structure of the Prussian blue material prepared in Example 3 of the present invention.

[0031] Fig.12 This is an electron microscope image of the Prussian blue material prepared in Example 3 of the present invention.

[0032] Fig.13 This is a comparison chart of the IC cycle performance of sodium ion batteries assembled with the Prussian blue gradient positive electrode material prepared in Example 3 of the present invention and the non-gradient positive electrode material of the same component.

[0033] Fig.14 This is a comparison chart of the moisture content of the sodium ion soft-pack battery cell electrode piece assembled with the Prussian blue gradient positive electrode material prepared in Example 3 of the present invention (right) and the sodium ion soft-pack battery cell electrode piece assembled with the non-gradient positive electrode material of the same component (left) and the gas production after high-temperature storage at 60°C. DETAILED DESCRIPTION

[0034] The present invention will now be further described with reference to the accompanying drawings and specific implementation methods.

[0035] Contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field. In the description of the present invention, it should be understood that the orientation or position relationship indicated by the terms "center", "upper", "lower", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", "counterclockwise", etc. are based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.

[0036] Embodiment 1:

[0037] A method for preparing a Prussian blue material provided in this embodiment comprises the following steps:

[0038] S1: Prepare a sodium ferrocyanide (Na4Fe(CN)6) solution with a molar concentration of 0.2 mol / L as raw material A, the temperature of raw material A is 50°C, and prepare a potassium ferrocyanide (K4Fe(CN)6) solution with a molar concentration of 0.2 mol / L as doped solution C. Prepare a manganese sulfate (MnSO4) solution with a molar concentration of 0.2 mol / L as raw material B, and prepare a ferrous sulfate (FeSO4) solution with a molar concentration of 0.2 mol / L as doped solution D. The temperature of raw material A is limited to improve the solubility, especially raw material A with a molar concentration of >0.3 mol / L, which needs to be heated to be completely dissolved.

[0039] S2: Add ultrapure water and 100g trisodium citrate complexing agent as the bottom liquid to a 1L reactor, the bottom liquid volume is 30% of the full reactor volume, use water bath heating, the precipitation temperature is 60°C, nitrogen is passed into the reactor, and raw materials A and B are fed after 2 hours of nitrogen, and quantitative raw materials A and quantitative raw materials B are continuously added to the bottom liquid by co-current dropwise addition, and stirred and mixed to form a precipitate. The dropwise addition speed is 40mL / h, and the stirring speed is 40rpm.

[0040] S3: Synthetic device such as Figure 1As shown, when the precipitation time reaches 3h, the potassium ferrocyanide (K4Fe(CN)6) solution pump corresponding to raw material A and the ferrous sulfate (FeSO4) solution pump corresponding to raw material B are turned on, and the potassium ferrocyanide (K4Fe(CN)6) solution is continuously added to the sodium ferrocyanide (Na4Fe(CN)6) solution at a dropping rate of 100mL / h, and the ferrous sulfate (FeSO4) solution is continuously added to the manganese sulfate (MnSO4) solution at a dropping rate of 40mL / h. The feed rate of raw materials A and raw material B added to the base liquid remains unchanged. At this time, the sodium ion content in raw material A gradually decreases, and the potassium ion content increases linearly. The manganese ion content in raw material B gradually decreases, and the ferrous ion content increases linearly. When all indicators in the precipitation process meet the requirements, the feeding can be stopped, the precipitation is completed, and the Prussian blue material is obtained.

[0041] Since the dropping speed of ferrous sulfate solution is slower than that of potassium ferrocyanide solution, the slope of potassium ion gradient on the surface of the product is greater than that of ferrous ion. The molecular formula of the Prussian blue material was determined to be Na by inductively coupled plasma emission spectrometry (ICP) and carbon and sulfur element analyzer. 1.85 K 0.15 Mn 0.8 Fe 0.2 Fe(CN)6.

[0042] The Prussian blue material obtained in this embodiment is a surface double gradient material, the core has no doped elements, only the concentration gradient changes on the surface of the material, and the change trends of the two elements are inconsistent. After the precipitation time reaches 4h, the particle size of the Prussian blue material is tested to be D50=3.0μm, and the reaction is stopped. After aging for 12h, the materials in the reactor are washed with ultrapure water, and then vacuum dried in a vacuum oven at 180℃ for 48h. The finished product is obtained after grinding. The cost color is off-white (Prussian white). It is mixed with non-gradient Na 1.85 K 0.15 Mn 0.8 Fe 0.2 Fe(CN)6 was placed under 60% humidity for observation of the color and moisture absorption weight gain. The results are as follows: Figure 2 As shown in the figure, the color of the gradient material is still basically grayish white, and the moisture content after 4 hours is only 0.6%, which is much better than the non-gradient material. Figure 3 and Figure 4 As shown, the morphology is single crystal cubic particles, and the color is white. Figure 5 As shown, there are only Na and Mn elements in the inner core, and K and Fe in the outer core begin to increase slowly linearly, and the slopes of the two elements are different, with the slope of Fe element being greater than that of K element.

[0043] This embodiment also provides an application of the Prussian blue material prepared by the above-mentioned method for preparing the Prussian blue material in preparing a positive electrode material for a battery.

[0044] The Prussian blue material prepared in this example was weighed according to the mass ratio of Prussian blue: carbon black (Super-P): PVDF = 85:10:5, and NMP solvent was added to prepare a slurry with a suitable viscosity. 2 It is evenly coated on the carbon-coated aluminum foil in an amount of , and then after roller pressing and vacuum drying at 130°C for 12 hours, it is cut into pole pieces with a diameter of 10 mm.

[0045] The electrode pieces prepared above were assembled into a 2016 button half-cell, the separator was GF / D (purchased from Duoduo Reagent), the counter electrode was a sodium sheet (self-made), the electrolyte was 1M NaPF6, and the volume ratio was 1:1 EC / DEC + 5% FEC. The half-cell assembled in this example was charged and discharged at 1C (150mA / g), the charge and discharge range was 2-4.0V, and the cycle capacity was tested. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that the half-cell assembled from the Prussian blue gradient positive electrode material synthesized in this embodiment has a first-cycle discharge capacity of 127.9 mAh / g, a capacity of 108.4 mAh / g after 400 cycles, and a capacity retention rate of 84.8%. The first-cycle capacity of the non-gradient material is only 115.8 mAh / g, and the capacity retention rate after 400 cycles is 59.9%, indicating that the multi-gradient material has better gram capacity and cycle performance than conventional materials.

[0046] Embodiment 2:

[0047] A method for preparing a Prussian blue material provided in this embodiment comprises the following steps:

[0048] S1: Prepare a potassium ferrocyanide (K4Fe(CN)6) solution with a molar concentration of 0.3 mol / L as raw material A, the temperature of raw material A is 60°C, and prepare a sodium ferrocyanide (Na4Fe(CN)6) solution with a molar concentration of 0.3 mol / L as doped solution C. Prepare a ferrous sulfate (FeSO4) solution with a molar concentration of 0.6 mol / L as raw material B, and prepare a zinc sulfate (ZnSO4) solution with a molar concentration of 0.6 mol / L as doped solution D.

[0049] S2: Add ultrapure water, 30g trisodium citrate complexing agent and 2mol / L potassium sulfate solution as the bottom liquid to a 1L reactor, the bottom liquid volume is 30% of the full reactor volume, the precipitation temperature is room temperature, nitrogen is passed through the reactor, and raw materials A and raw materials B are fed after 6 hours of nitrogen passing, and a certain amount of raw materials A and a certain amount of raw materials B are continuously added to the bottom liquid by co-current dropwise addition, and stirred and mixed to form a precipitate. The dropping speed is 40mL / h and the stirring speed is 100rpm.

[0050] S3: When the precipitation starts, the sodium ferrocyanide (Na4Fe(CN)6) solution pump corresponding to raw material A and the zinc sulfate (ZnSO4) solution pump corresponding to raw material B are turned on, and the potassium ferrocyanide (K4Fe(CN)6) solution is continuously added to the potassium ferrocyanide (K4Fe(CN)6) solution at a drop rate of 10mL / h, and the ferrous sulfate (FeSO4) solution is continuously added to the ferrous sulfate (FeSO4) solution at a drop rate of 10mL / h. The feed rate of raw materials A and raw materials B added to the base liquid remains unchanged. At this time, the potassium ion content in raw material A gradually decreases, and the sodium ion content increases linearly. The ferrous ion content in raw material B gradually decreases, and the zinc ion content increases linearly. When all indicators in the precipitation process meet the requirements, the feeding can be stopped, the precipitation is completed, and a Prussian blue material is obtained.

[0051] Since the base liquid already contains a high concentration of potassium ions, the slope of the potassium ion gradient on the surface of the final product is lower than that of ferrous ions. The molecular formula of the Prussian blue material was determined to be K by inductively coupled plasma emission spectrometry (ICP) and carbon and sulfur element analyzer. 1.82 Na 0.18 Fe 0.6 Zn 0.4 (Fe(CN)6, finished product structure is as follows Figure 7 shown.

[0052] The Prussian blue material obtained in this embodiment is a full-process dual-gradient material. The material shows a concentration gradient change from the core to the surface, and the change trends of the two elements are inconsistent. After the precipitation time reaches 5h, the particle size of the Prussian blue material is tested to be D50=4.0μm, and the reaction is stopped. The materials in the reactor are not aged, but directly washed and dried. The final concentration gradient change diagram of the Prussian blue material is shown in Figure 8 shown.

[0053] The chemical formula of the Prussian blue material prepared in this embodiment is K 1.82 Na 0.18 Fe 0.6 Zn 0.4(Fe(CN)6, and non-gradient conventional materials of the same components were prepared and battery pole pieces were prepared together for comparison. The battery assembly process is the same as in Example 1, except that a potassium ion battery is assembled in this embodiment, the negative electrode is a potassium sheet (self-made), the electrolyte solute is 1MKPF6, and the volume ratio is 1:1 EC / DEC+2% FEC. The half-cell assembled in this embodiment is charged and discharged at 1C (150mA / g), the charge and discharge interval is 2-4.0V, and the cycle capacity is tested. The results are as follows Fig. 9 As shown. It can be seen from the figure that the potassium ion battery assembled from the Prussian blue positive electrode material synthesized in this embodiment has a first-cycle discharge capacity of 85.6 mAh / g, a capacity of 77.5 mAh / g after 400 cycles, and a capacity retention rate of 90.5%. Although the first-cycle capacity of the conventional non-gradient material is 88.8 mAh / g, it is relatively high, but the capacity after 400 cycles is only 59.3 mAh / g, and the cycle retention rate is 66.8%, which is lower than that of the gradient material, indicating that the cycle stability of the gradient Prussian blue potassium ion battery has also been improved.

[0054] Embodiment three:

[0055] A method for preparing a Prussian blue material provided in this embodiment comprises the following steps:

[0056] S1: Prepare a sodium ferrocyanide (Na4Fe(CN)6) solution with a molar concentration of 0.2 mol / L as raw material A, the temperature of raw material A is 40°C, and prepare a potassium ferrocyanide (K4Fe(CN)6) solution with a molar concentration of 0.2 mol / L as doped solution C. Prepare a manganese sulfate (MnSO4) solution with a molar concentration of 0.2 mol / L as raw material B, and prepare a ferrous sulfate (FeSO4) solution with a molar concentration of 0.2 mol / L as doped solution D.

[0057] S2: Add ultrapure water, 40g trisodium citrate complexing agent and 1mol / L sodium sulfate solution as the bottom liquid to a 1L reactor, the bottom liquid volume is 30% of the full reactor volume, the precipitation temperature is 60°C, nitrogen is passed into the reactor, and raw materials A and raw materials B are fed after 3 hours of nitrogen passing, and a certain amount of raw materials A and a certain amount of raw materials B are continuously added to the bottom liquid by co-current dropwise addition, and stirred and mixed to form a precipitate. The dropping speed is 30mL / h, and the stirring speed is 600rpm.

[0058] S3: After the precipitation starts, the sodium ferrocyanide (Na4Fe(CN)6) solution pump corresponding to raw material A and the zinc sulfate (ZnSO4) solution pump corresponding to raw material B are turned on, and the potassium ferrocyanide (K4Fe(CN)6) solution is continuously added to the potassium ferrocyanide (K4Fe(CN)6) solution at a drop rate of 5mL / h, and the ferrous sulfate (FeSO4) solution is continuously added to the ferrous sulfate (FeSO4) solution at a drop rate of 10mL / h. The feed rate of raw materials A and raw materials B added to the base solution remains unchanged. After 2 hours of precipitation, the drop rate of the doped solution C is increased to 10mL / h, and the drop rate of the doped solution D is increased to 15mL / h. In this way, the sodium ion content in raw material A gradually decreases during the entire precipitation process, such as Fig.10 As shown, the potassium ion content increases linearly and presents two different gradients of concentration changes. The manganese ion content and the ferrous ion content in the raw material B also have the same trend, but the gradient slopes of the potassium ion and the ferrous ion changes are inconsistent. The final product is a double-pass double-gradient type. The material presents a concentration gradient change from the inner core to the surface. The change trend of a single element in the front and back halves is inconsistent, and the change trends of the two elements are also inconsistent. The feeding can be stopped until all indicators in the precipitation process meet the requirements, and the precipitation is completed to obtain a Prussian blue material.

[0059] After the precipitation time reaches 6 hours, the particle size of the Prussian blue material is tested to be D50 = 10.0 μm, and the reaction is stopped. The materials in the reactor are not aged, but directly washed and dried. The molecular formula of the Prussian blue material obtained is determined by inductively coupled plasma emission spectrometry (ICP) and carbon and sulfur element analyzer to be Na 1.78 K 0.22 Mn 0.72 Fe 0.28 Fe(CN)6. Finished products such as Fig.11 and Fig.12 As shown. Non-gradient conventional materials with the same components were prepared and battery electrodes were prepared together for comparison of electrochemical performance.

[0060] The chemical formula of the Prussian blue material prepared in this embodiment is Na 1.78 K 0.22 Mn 0.72 Fe 0.28 Fe(CN)6, assembled into a soft-pack full battery (240mAH), the full battery pole piece and assembly process are as follows: The Prussian blue material prepared in this embodiment is Prussian blue: carbon black (Super-P): PVDF = 90:6:4. Weigh each raw material, add NMP solvent to prepare a slurry with appropriate viscosity, and mix at 10mg / cm 2The amount of the material was evenly coated on the aluminum foil, and then after roller pressing and vacuum drying at 130°C for 24 hours, it was cut into 41*76mm positive electrode sheets; the negative electrode material was weighed according to the mass ratio of hard carbon: carbon black (Super-P): PVDF = 94:4:2, and the raw materials were weighed according to 3mg / cm 2 It is evenly coated on aluminum foil in an amount of , and then after roller pressing and vacuum drying at 130°C for 24 hours, it is cut into negative electrode sheets of 41.5*76.5mm in size.

[0061] The above-prepared electrode stacking process was assembled into a soft pack battery, the separator was PE (purchased from Duoduo Reagent), the electrolyte was 1M NaPF6, and the volume ratio was 1:1 EC / DEC + 5% FEC (purchased from Duoduo Reagent). The full battery assembled in this example was charged and discharged at 10C (2.4A), and the charge and discharge range was 2.2-3.65V to test the cycle capacity. The results are as follows Fig.13 As shown. It can be seen from the figure: the full battery assembled from the Prussian blue positive electrode material synthesized in this embodiment has a first-cycle discharge capacity of 226.0mAh, a capacity of 203.1mAh after 600 cycles, and a capacity retention rate of 89.9%. The first-cycle discharge capacity of the soft-pack battery prepared with conventional materials is only 197.9mAh, and the capacity after 600 cycles is 155mAh, with a capacity retention rate of 78.3%. The full battery prepared with gradient materials has obvious improvements in capacity and cycle performance. In addition, the moisture-proof performance of the gradient material is also improved due to the gradient doping of potassium ions, etc. Fig.14 This shows the changes in the soft-pack battery cells when stored at a high temperature of 60°C. The excellent moisture-proof properties and extremely low moisture content of the gradient material prevent the soft-pack battery cells from bloating at high temperatures.

[0062] The present invention can achieve different gradient changes of dual doping elements inside the material by regulating the speed of adding doping elements to raw materials A and raw material B during the precipitation process, such as the concentration change speeds of the alkali metal element core and the surface are inconsistent, and the concentration change speeds of the alkali metal element and the transition metal element are different, thereby more accurately regulating the electrochemical properties and moisture-proof properties of the material.

[0063] A solution including ferrocyanide as raw material A and a solution including transition metal salt as raw material B are continuously added to the reaction base liquid, and these two raw materials are simultaneously added to the reactor in parallel, and the solution of the element to be doped is continuously added to the raw material A and the raw material B during the reaction process, thereby realizing a multi-gradient change in the concentration of elements such as Na, K and elements such as Mn, Fe, Co, Ni, Zn, and Cu.

[0064] By adopting the controlled crystallization precipitation method to synthesize cubic or spherical Prussian blue particles, the particle size increases with the precipitation time, and the newly generated crystal nuclei are adsorbed on the original crystal nuclei and grow up without secondary nucleation alone, thereby ensuring that the gradient change trend of the raw material and the gradient change trend of the particles are consistent.

[0065] The Prussian blue materials prepared by the method of the present invention can be divided into the following six types of gradient materials:

[0066] 1. Surface single gradient type, which shows concentration gradient change only on the surface of the material, and the change trends of the two elements are consistent;

[0067] 2. Surface double gradient type, which only shows concentration gradient changes on the surface of the material, and the change trends of the two elements are inconsistent;

[0068] 3. Full-process single gradient type, the material presents a concentration gradient change from the core to the surface, and the change trends of the two elements are consistent;

[0069] 4. Full-process dual-gradient type, the material presents a concentration gradient change from the core to the surface, and the change trends of the two elements are inconsistent;

[0070] 5. Double-pass single gradient type: the material shows a concentration gradient change from the core to the surface. The change trend of a single element in the first and second half is inconsistent, while the change trend of the two elements is consistent.

[0071] 6. Dual-path dual-gradient type: the material shows a concentration gradient change from the core to the surface. The change trend of a single element in the front and back half is inconsistent, and the change trends of the two elements are also inconsistent.

[0072] The gradient-type Prussian blue derivative positive electrode material synthesized by the method of the present invention is compared with conventional non-gradient materials under the same proportion and composition. The sodium and manganese elements in the core improve the material's gram capacity and voltage platform, the potassium element on the surface improves the material's moisture resistance, and the nickel, cobalt, zinc, copper, iron and other elements on the surface improve the material surface stability and battery cycle performance. The precipitation process is adopted, and the surface modification is completed directly in the precipitation process through the gradient change of alkali metal ions and variable valence transition metal ions from the bulk phase to the surface during the precipitation process, without the need for a subsequent wet coating process, and the surface modification effect is more uniform. The gradient change speed of various metal ions can be adjusted in real time to obtain a product with multiple elements and multiple concentration gradient changes, thereby obtaining a modification effect that is superior to the direct doping of traditional battery materials in raw materials and the coating of finished products, greatly improving the moisture resistance, rate performance, and cycle stability of Prussian blue materials.

[0073] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it should be understood by those skilled in the art that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a Prussian blue material, characterized in that: The following steps are involved: S1: preparing a solution including ferrocyanide as raw material A, preparing a solution including a transition metal salt as raw material B, preparing a solution C to be doped including alkali metal ions, and preparing a solution D to be doped including transition metal ions; S2: Adding a base liquid into a container, continuously adding raw material A and raw material B into the base liquid, and stirring and mixing to form a precipitate; S3: During the precipitation process, the doped solution C is continuously added to the raw material A so that the concentration of the alkali metal ions in the raw material A changes gradually, and the doped solution D is continuously added to the raw material B so that the concentration of the transition metal ions in the raw material B changes gradually, until the precipitation is completed to obtain a Prussian blue material.

2. The method for preparing a Prussian blue material according to claim 1, characterized in that: Raw material A includes at least one of sodium ferrocyanide solution, potassium ferrocyanide solution and lithium ferrocyanide solution, with a molar concentration of 0.1-1 mol / L, and a temperature of raw material A of 20-80° C.; Raw material B includes one or more mixed solutions of sulfates of manganese, iron, cobalt, nickel, zinc and copper, with a molar concentration of 0.1-3 mol / L; The total molar concentration of alkali metal ions in the doped solution C is 0.1-1 mol / L; The total molar concentration of transition metal ions in the doping solution D is 0.1-3 mol / L.

3. The method for preparing a Prussian blue material according to claim 1, characterized in that: The doping ions in the doped solution C include at least one of potassium ions, sodium ions, and lithium ions; The doping ions in the doped solution D include at least one of manganese ions, iron ions, ferrous ions, cobalt ions, zinc ions, and copper ions.

4. The method for preparing a Prussian blue material according to claim 1, characterized in that: In step S2, a quantitative amount of raw material A and a quantitative amount of raw material B are continuously added to the base liquid by a co-current dropwise addition method; The precipitation method is intermittent, continuous or semi-continuous; The precipitation period is 1-40h, and the precipitation temperature is from room temperature to 80℃; The stirring speed is 10-1000 rpm.

5. The method for preparing a Prussian blue material according to claim 4, characterized in that: The precipitation period is 3-10h, and the precipitation temperature is from room temperature to 60°C.

6. The method for preparing a Prussian blue material according to claim 4, characterized in that: The dropping speed of raw material A and raw material B is 30-45 mL / h; The drop rate of the doped solution C is 5-110 mL / h; The drop rate of the doped solution D is 10-45 mL / h.

7. The method for preparing a Prussian blue material according to claim 1, characterized in that: In step S2, after adding the base liquid, add a reducing agent, an inert gas, a reducing gas, or a mixture of an inert gas and a reducing gas into the container, and then add raw material A and raw material B after 2-6 hours; The inert gas is nitrogen or argon, the reducing gas is hydrogen or carbon monoxide, and the reducing agent is ascorbic acid, hydrazine hydrate, sodium sulfite or sodium borohydride.

8. The method for preparing a Prussian blue material according to claim 1, characterized in that: The base liquid is an aqueous solution, a sodium sulfate solution, a sodium chloride solution or a potassium sulfate solution, and the base liquid temperature is from room temperature to 100°C; The mass concentration of the sodium sulfate solution, sodium chloride solution or potassium sulfate solution is 200-450 g / L.

9. The method for preparing a Prussian blue material according to claim 8, characterized in that: The base solution also includes a complexing agent with a mass concentration of 0.1-10 g / L; The complexing agent is at least one of trisodium citrate, ammonia water, sodium oxalate, sodium phosphate, sodium pyrophosphate, sodium acetate, ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, sodium manganese ethylenediaminetetraacetate, triethanolethylenediamine, urea, sodium succinate, sodium tartrate, polyvinylpyrrolidone, and polyacrylamine.

10. Use of the Prussian blue material prepared by the method for preparing the Prussian blue material according to any one of claims 1 to 9 in preparing a positive electrode material for a battery.

Citation Information

Patent Citations

  • A method for preparing a lithium-ion battery cathode material and its application

    CN106207138B

  • Lithium ion battery positive electrode material with full-gradient concentration distribution and preparation method thereof

    CN111653742A

Cited By

  • Prussian blue compound as well as preparation method and application thereof

    CN120736539A

  • Prussian-blue-like additive for vanadium electrolyte as well as preparation method and application of Prussian-blue-like additive

    CN121225619A

  • A prussian blue-like additive for vanadium electrolyte and a preparation method and application thereof

    CN121225619B

  • Rubidium and cesium adsorbent as well as preparation method and application thereof

    CN121372304A

  • High-crystallinity prussian blue positive electrode material and preparation method thereof

    CN122464435A